Synthesis and Characterization of Nano Chitosan from Vannamei Shrimp Shell (Litopenaeus vannamei) - Dian Wijaya Kurniawidi; Siti Alaa; Eva Nurhaliza; Desti Olga Safitri; Susi Rahayu; Muhamad Ali; Muhamad Amin (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research